Democratic Republic of the Congo : Joint Staff Advisory Note. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
This Joint Advisory Note on the Democratic Republic of the Congo discusses economic growth and employment-creating sectors. The agriculture and mining sectors are projected to continue their expansion, while simultaneously raising labor productivity and freeing up labor. The urban population is expected to reach 40 million by 2025, up from an estimated 24 million in 2012. Some of these urban centers will function as service centers for rural areas, but they will be increasingly integrated with international markets through formal and informal trade, partly as a result of better telecommunications. The government's objective is to boost mining output, and the sector's contribution to fiscal revenues requires an increase in foreign investment, an improvement in the business climate, and a strengthening of governance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet